2002
DOI: 10.1530/eje.0.1470275
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa in female adolescents: endocrine and bone mineral density disturbances

Abstract: Anorexia nervosa (AN) is a chronic childhood psychiatric illness that involves a reduction in caloric intake, loss of weight and amenorrhea, either primary or secondary. The diagnostic criteria for AN have been established by the American Psychiatric Association. The prevalence of this disease amongst adolescents and young adults is between 0.5 and 1% and the incidence of new cases per year is approximately 5-10/100 000 between 15 and 19 years of age. A number of endocrine and metabolic disturbances have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
16

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 127 publications
2
90
0
16
Order By: Relevance
“…Girls with AN usually exhibit suppression of bone formation and resorption markers, which correlates with BMI and/or BMD, and indicates a decrease in bone turnover [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. It was also observed that an increase in serum OPG correlated negatively with BMI and/or BMD [51,[58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Girls with AN usually exhibit suppression of bone formation and resorption markers, which correlates with BMI and/or BMD, and indicates a decrease in bone turnover [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. It was also observed that an increase in serum OPG correlated negatively with BMI and/or BMD [51,[58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…That extremely low adiposity as seen with anorexia nervosa and extreme physical activity is associated with late pubertal timing is well established (14,15). In contrast, to what extent overweight and obesity is associated with early pubertal timing is more controversial.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that neuropeptide Y signaling could have a role in both central and local neural control of bone remodeling. Neuropeptide Y signaling has been linked to food intake and like leptin, there are links between neuropeptide Y signaling and obesity (Munoz and Argente, 2002;Feletou and Levens, 2005). Neuropeptide Y receptors are found on pre-and post-synaptic neurons.…”
Section: Central Control Of Bone Remodelingmentioning
confidence: 99%